KEBIJAKAN TRANSPORTASI KERETA CEPAT JAKARTA BANDUNG DALAM MEWUJUDKAN ANGKUTAN RAMAH LINGKUNGAN - Muh Kadarisman (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2017)
The objective of this research is to analyze the feasibility of Jakarta-Bandung Fast Train Transportation policy in realizing environmentally friendly transportation. The research uses qualitative methods, because it intends to get empirical facts, find deep meaning, observe, capture reality and examine the behavior of indifidu and group of research object. Instruments with interviews, focus group discussion, observation, and triangulation. Determination of Informant with purposive technique. Data analysis with emic, ethical approach and verstehen. The results of research: 1. Jakarta and Bandung as the first and third largest cities with very high economic potential, hence, the policy of the Government decided the construction of Jakarta-Bandung Fast Train infrastructure is appropriate. The fast train became the preferred form of modernization of mass transportation in building inter-city connectivity between provinces, and regional development. 2. The rapid railway development of Jakarta-Bandung is in the framework of moving large quantities of people or goods within a short time, creating optimal employment, creating the railway industry using local materials, and technology transfer. 3. With the substitution of the type of movement of conventional and highway-based racecars to fast trains with electric power, thereby reducing carbon emissions through emission reduction. Renewable energy sources.